2012
DOI: 10.1038/cmi.2012.48
|View full text |Cite
|
Sign up to set email alerts
|

The equivalents of human blood and spleen dendritic cell subtypes can be generated in vitro from human CD34+ stem cells in the presence of fms-like tyrosine kinase 3 ligand and thrombopoietin

Abstract: Dendritic cells (DCs) are immune cells specialized to capture, process and present antigen to T cells in order to initiate an appropriate adaptive immune response. The study of mouse DC has revealed a heterogeneous population of cells that differ in their development, surface phenotype and function. The study of human blood and spleen has shown the presence of two subsets of conventional DC including the CD1b/c 1 and CD141 1 CLEC9A 1 conventional DC (cDC) and a plasmacytoid DC (pDC) that is CD304 1 CD123 1 . S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 54 publications
0
44
1
Order By: Relevance
“…So far, a proper culture for this purpose has not been established. The widely used GM-CSF culture produces monocyte-derived DC that differs from the authentic DCs (Cheong et al, 2010; Crozat et al, 2010; Naik et al, 2006; Xu et al, 2007); a two-step cytokine cocktail culture produces large amount of cDCs but no pDCs (Doulatov et al, 2010; Poulin et al, 2010); several stromal cell cultures have been used to produce pDCs but their production of two cDC subsets, myeloid or lymphoid cells was not evaluated (Chicha et al, 2004; Proietto et al, 2012). Here we report how we establish and optimize a culture system of stromal cell and cytokines that enables simultaneous differentiation of three DC subsets, monocytes, granulocytes and lymphocytes at a single cell level.…”
Section: Introductionmentioning
confidence: 99%
“…So far, a proper culture for this purpose has not been established. The widely used GM-CSF culture produces monocyte-derived DC that differs from the authentic DCs (Cheong et al, 2010; Crozat et al, 2010; Naik et al, 2006; Xu et al, 2007); a two-step cytokine cocktail culture produces large amount of cDCs but no pDCs (Doulatov et al, 2010; Poulin et al, 2010); several stromal cell cultures have been used to produce pDCs but their production of two cDC subsets, myeloid or lymphoid cells was not evaluated (Chicha et al, 2004; Proietto et al, 2012). Here we report how we establish and optimize a culture system of stromal cell and cytokines that enables simultaneous differentiation of three DC subsets, monocytes, granulocytes and lymphocytes at a single cell level.…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression profiling and/or ontogenic studies showed that MoDC, Langerhans cell, and DC lines strikingly differ from LT-DC subsets and are more similar to monocytes or macrophages (4,(29)(30)(31)(32). Cultures of CD34 + progenitors with FLT3-ligand (FLT3-L) or thrombopoietin (TPO) have been reported to yield pDC, CD141 + CLEC9A + DC, or CD1c + DC (11,33,34). The extent to which the CD141 + CLEC9A + , the CD1c + , or the other HLA-DR + cells in these cultures resembled human bDC subsets was, however, not thoroughly examined.…”
mentioning
confidence: 99%
“…They comprise approximately 1 % of circulating peripheral blood mononuclear cells (PBMC) and are classically defined as Ag-presenting leukocytes that lack other leukocyte lineage markers (CD3, 14,15,15,19,20,56), express high levels of major histocompatibility complex (MHC) class II (HLA-DR) molecules (lineage -HLA-DR ? ) and have potent allo-stimulatory capacity [4,5].…”
Section: Human Dendritic Cellsmentioning
confidence: 99%
“…DC express fms-like tyrosine kinase 3 (Flt3) and they can be differentiated by Flt3 ligand (Flt3L) from human CD34? progenitors in vitro [18,20] and in vivo [21], suggesting a dependence on Flt3L for development, like their mouse counterparts. The requirement for transcription factors is less clear.…”
Section: Human Dendritic Cellsmentioning
confidence: 99%